PENGARUH MEDIA BAAMBOOZLE TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Baamboozle learning media on students' critical thinking skills in elementary school. This research used a quantitative approach with a pre-experimental design in the form of a one-group pretest–posttest design. The research was conducted on fifth-grade students of SDN Nagasari II. Data collection techniques were carried out using pretest and posttest instruments to measure students’ critical thinking abilities before and after the implementation of the Baamboozle media. The data analysis technique used normality tests and paired sample t-tests. The results showed that the use of Baamboozle learning media had a significant effect on improving students' critical thinking skills. This is indicated by the results of the paired sample t-test which showed a significance value of 0.000 (p < 0.05), meaning that there was a significant difference between the pretest and posttest results. Thus, the Baamboozle learning media can be used as an interactive learning medium that helps increase student engagement and supports the development of critical thinking skills in elementary school learning.